METABOLIC CONTROL AND BODY COMPOSITION OF CHILDREN AND ADOLESCENTS WITH PHENYLKETONURIA - Zeni Drubi Nogueira; Ney Boa-Sorte; Maria Efigênia de Queiroz Leite; Maria Betânia Pereira Toralles; Tatiana Amorim (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To characterize metabolic control and verify whether it has any relation with socioeconomic, demographic, and body composition variables in children and adolescents with phenylketonuria (PKU) diagnosed in the neonatal period. Methods: This cohort study collected retrospective data of 53 phenylketonuric children and adolescents. Data on family income, housing, and mother's age and schooling level were collected, and anthropometric measures of body composition and distribution were taken. All dosages of phenylalanine (Phe) from the last five years (2015-2019) were evaluated and classified regarding their adequacy (cutoffs: 0-12 years: 2-6 mg/dL; 12-19 years: 2-10 mg/dL). Adequate metabolic control was considered if ≥7%) of the dosages were within desired ranges. Results: The mean (±standard deviation) age in the last year was 10.1±4.6 years. Most of them were under 12 years old (33/53; 62.3%) and had the classic form of the disease (39/53; 73.6%). Better metabolic control was observed among adolescents (68.4 versus 51.4%; p=0.019). Overweight was found in 9/53 (17%) and higher serum Phe levels (p<0.001) were found in this group of patients. Metabolic control with 70% or more Phe level adequacy decreased along with the arm muscle area (AMA) (ptendency=0.042), being 70.0% among those with low reserve (low AMA), and 18.5% among those with excessive reserve (high AMA). Conclusions: Adequate metabolic control was observed in most patients. The findings suggest that, in this sample, the levels of phenylalanine may be related to changes in body composition.